The Correlation between Self-Efficacy and Pedagogic Competence with Teacher Teaching Effectiveness (Research on Science Teachers at Private Vocational High Schools, Citeureup District, Bogor) - Four Meiyanti; Soewarto Hardienata; Nandang Hidayat (Pedagonal : Jurnal Ilmiah Pendidikan, 2022)
This research was conducted in private vocational schools in Citeureup district, Bogor in 2014 with a total sample of 81 science teachers in private vocational schools taken proportionally by random sampling. This study uses correlational research methods and data analysis techniques using statistical tests and simple linear regression as well as multiple linear regression correlations and partial correlation tests. The hypothesis testing was carried out at a significant level of 0.01 and 0.05. The results of the study establish three conclusions, namely: First, there is a significant positive relationship between self-efficacy and teacher teaching effectiveness which is expressed in the equation = 50.350 + 0.627 X1 and the correlation coefficient ry1 is 0.982 and the determinant coefficient r2y1 is 0.964. Second: there is a significant positive relationship between pedagogic competence and teacher teaching effectiveness which is expressed in the equation = 102.83 + 1.553 X2 and the correlation coefficient ry2 is 0.973 and the coefficient of determination r2y2 is 0.947. Third: there is a significant positive relationship between self-efficacy and pedagogic competence together with teacher teaching effectiveness which is expressed in the equation Ŷ = 66.070 + 0.436 X1 + 0.489 X2 and the correlation coefficient ry1.2 is 0.984 and the coefficient of double determination is r2y1.2 of 0.964. The conclusion that can be drawn is that the effectiveness of teacher teaching can be increased through increasing self-efficacy and pedagogic competence